2020
DOI: 10.5194/hess-2020-242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the large-scale plant-water relations using remote sensing products in the humid subtropical Pearl River Basin in south China

Abstract: Abstract. Vegetation interact closely with water resources. Conventional studies of plant-water relations at the field scale are fundamental for understanding the mechanisms of how plants alter and adapt to environmental changes, while large-scale studies can be more practical for regional land use and water management towards mitigating climate change impacts. In this study, we investigated the changes in total water storage (TWS), aridity index (AI) and vegetation greenness, productivity and their interactio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Using the GRACE satellite, Zhao et al [11] investigated the impact of ecological restoration on TWS in northern China from 1982 to 2016. Wang et al [20] suggested that vegetation was more strongly affected by TWS than precipitation on both the annual and monthly scales in the Pearl River basin from 2002 to 2015. In addition to the effects of vegetation, climate change and human activities were altering the hydrological cycle with significant consequences for TWS.…”
Section: Introductionmentioning
confidence: 99%
“…Using the GRACE satellite, Zhao et al [11] investigated the impact of ecological restoration on TWS in northern China from 1982 to 2016. Wang et al [20] suggested that vegetation was more strongly affected by TWS than precipitation on both the annual and monthly scales in the Pearl River basin from 2002 to 2015. In addition to the effects of vegetation, climate change and human activities were altering the hydrological cycle with significant consequences for TWS.…”
Section: Introductionmentioning
confidence: 99%